Reactive pollutants dispersion modeling in a street canyon - Merah, Aissa; Noureddine, Abdelkader (Zielona Góra: Uniwersytet Zielonogórski)
Reactive pollutant dispersion in a 3-D urban street canyon is numerically investigated using a computational fluid dynamics (CFD) code (Ansys-CFX) and includes transport equations for NO, NO2, and O3 with simple photochemistry. An area emission source of NO and NO2 was considered in the presence of background O3 with an ambient wind perpendicular to the along-canyon direction.
Keywords: street canyon; reactive pollutant; computational fluid dynamics (CFD)